Analisa Kemampuan Penyesuain Diri Mahasiswa Asuransi dan Aktuaria Terhadap Kurikulum Pendidikan Vokasi - Debrina Vita Ferezagia (Jurnal Sosial Humaniora Terapan, 2019)
This study aims to analyze the ability of Vocational students to change the Vocational Education curriculum. Kurikukum Vocational education better known as curriculum 3,2,1 resulted in teaching and learning activities that changed dramatically. The data used is sourced from primary data by distributing questionnaires to 50 Insurance and Actuarial students. The questionnaire used was the result of previous research by Baker and Siry (1984). The measuring instrument used is Student Adaptation to Collage Quisionnaire (SACQ). The SACQ indicator variable consists of 21 question items. The measurement scale used is the linker scale with a score of 1-9. After the data is collected, then it is analyzed descriptively. To make factors more general so that they are easy to classify, the authors use confirmatory factor analysis methods. The results obtained are 5 dominant factors that influence the ability of students to adapt, including emotional ability, social ability, institutional attachment to perguruan tinggi, motivation and academic environment. This research has theoretical implications for practical psychology. In addition, the results of this study provide policy to student managers to motivate students based on factors that are dominant in influencing students' ability to adapt.Keywords: adaptability, factor analysis, vocational curriculum